A method for preparing a seaweed biochar-derived carbon material

CN122977360APending Publication Date: 2026-10-27SHANDONG HAIXIANG BIOMEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611339788.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,现有技术对褐藻水热液化液相产物的利用多侧重于单一相组分,通常仅将分离得到的水相或油相单独用于改性或负载,未能围绕同一批次液相产物建立水相改性与油相负载相衔接的制备路线,因此,水相与油相之间的同源协同利用不足,矿物载体改性与有机组分负载之间的工艺衔接性较弱,不利于制备组成稳定和性能均一的复合碳材料

Benefits of technology

本发明将同一批次褐藻液相产物分离得到的水相和油相依次用于钠基膨润土的水相改性和后续油相负载,使矿物载体表面改性与有机组分引入在同一制备体系内连续完成,有利于提高液相产物的综合利用率,改善油相负载均匀性并降低水洗过程中的有机组分流失;经后续氮气气氛热处理后,所得材料具有较好的孔结构和吸附性能,并通过再活化处理实现重复利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977360A_ABST
    Figure CN122977360A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of seaweed biochar derived carbon material and relates to the technical field of seaweed-based adsorption material preparation. The method comprises the following steps: performing hydrothermal liquefaction on brown algae raw materials after cleaning, drying and crushing to obtain a liquid phase product; extracting the liquid phase product to obtain oil phase products and water phase products of the same batch; removing residual ethyl acetate from the water phase product, concentrating, adjusting the pH, and obtaining a water phase treatment liquid, which is used for water phase modification of sodium-based bentonite; preparing the oil phase product into an oil phase diluent and loading the oil phase diluent on the water phase modified bentonite intermediate, and then performing nitrogen atmosphere heat treatment to obtain seaweed biochar derived carbon material. The water phase and the oil phase obtained by separating the liquid phase products of the same batch are sequentially used in the same preparation batch, the utilization degree of the liquid phase products is improved, and the overallity and stability of the material preparation process are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of seaweed-based adsorbent material preparation technology, and in particular to a method for preparing seaweed biochar-derived carbon materials. Background Technology

[0002] In recent years, seaweed-based adsorbent materials and biochar have received continuous attention in the fields of organic pollutant removal, mineral composite carrier construction, and low-cost carbon material preparation. In existing technologies, marine biomass such as brown algae are usually used as carbon precursors after pyrolysis, hydrothermal carbonization, or hydrothermal liquefaction. Among them, the liquid products obtained by hydrothermal liquefaction contain a variety of organic components that can be further utilized, and are therefore gradually used in the preparation of modifiers, binder phases, or supported precursors. At the same time, layered silicate minerals such as bentonite are often used as inorganic carriers for composite carbon materials due to their interlayer structure and surface modifiability. Therefore, combining seaweed hydrothermal liquefaction products with bentonite has become a development direction in the preparation of seaweed-based functional materials.

[0003] However, existing technologies for utilizing the hydrothermal liquefaction liquid phase products of brown algae mostly focus on single-phase components. Typically, the separated aqueous or oil phases are used alone for modification or loading, failing to establish a preparation route that connects aqueous phase modification and oil phase loading around the same batch of liquid phase products. Therefore, there is insufficient synergistic utilization between the aqueous and oil phases, and the process connection between mineral carrier modification and organic component loading is weak, which is not conducive to the preparation of composite carbon materials with stable composition and uniform performance. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a method for preparing seaweed biochar-derived carbon materials, comprising the following steps: S1. The brown algae raw material is washed, dried and crushed, and then subjected to hydrothermal liquefaction to separate the liquid phase product; S2. The liquid phase product is extracted and separated by organic solvent to obtain an oil phase product and an aqueous phase product; The oil phase product and the aqueous phase product are obtained by separating the liquid phase product from the same batch; S3. Remove residual organic solvent from the aqueous product, concentrate it and adjust the pH to obtain an aqueous treatment solution; S4. Sodium-based bentonite is contacted with the aqueous treatment liquid to modify the sodium-based bentonite in aqueous phase, thereby obtaining an aqueous modified bentonite intermediate. S5. The oil phase product is prepared into an oil phase dilution, and after the aqueous phase modification is completed, it is added to the aqueous phase modified bentonite intermediate so that the oil phase product is loaded on the aqueous phase modified bentonite intermediate. The solvent in the oil phase dilution solution is removed to obtain the oil phase supported composite precursor; S6. The oil-supported composite precursor is heat-treated under a nitrogen atmosphere to obtain seaweed biochar-derived carbon materials.

[0005] Preferably, the brown algae raw material is kelp or Sargassum fusiforme; The brown algae raw material was washed four times with deionized water, dried at 65°C, pulverized, and passed through a 100-mesh sieve to obtain the seaweed powder.

[0006] Preferably, in S1, the mass ratio of the seaweed powder to water is 1:10; After the seaweed powder and water reactant is added to the sealed reactor, its liquid volume is 60% of the effective volume of the sealed reactor. Before the hydrothermal liquefaction reaction, nitrogen gas is introduced into the sealed reactor for 10 minutes, and the stirring speed during the hydrothermal liquefaction reaction is 400 r / min.

[0007] Preferably, in S2, the volume ratio of the liquid product to ethyl acetate is 1:2 for each extraction, and the extraction is performed a total of 3 times; The organic phases obtained from each extraction were combined and ethyl acetate was removed under reduced pressure to obtain the oil phase product. The aqueous phases obtained from each extraction are combined, and the residual organic phase is removed to obtain the aqueous product.

[0008] Preferably, in step S3, the pH of the aqueous product is adjusted using hydrochloric acid with a concentration of 1 mol / L; The pH-adjusted aqueous phase solution was allowed to stand at 35°C for 60 minutes.

[0009] Preferably, in S4, the ratio of sodium-based bentonite to the aqueous treatment solution is 1g:20mL; After adding the sodium-based bentonite to the aqueous treatment solution, the mixture was stirred at 45°C for 8 hours, and the pH of the system was maintained at 4.0 by adding hydrochloric acid. After stirring, the mixture was allowed to stand at 40°C for 24 hours, and the solid obtained from the solid-liquid separation was washed three times with deionized water at pH 4.0.

[0010] Preferably, in S4, the solid-liquid separation is performed by centrifugation at a speed of 5000 r / min for a time of 10 min.

[0011] Preferably, in S5, the mass ratio of the oil phase product to ethanol is 1:4; The oil phase diluent was added over a period of 45 minutes, and the stirring speed during the addition process was 500 r / min. After the addition was completed, stirring was continued at 60°C for 60 min, and ethanol was removed under reduced pressure at 60°C to obtain the oil-phase supported composite precursor.

[0012] Preferably, in step S6, the flow rate of the nitrogen gas is 150 mL / min; The temperature is increased to the heat treatment temperature at a heating rate of 3℃ / min; After the heat preservation is completed, the material is cooled to below 80°C in a nitrogen atmosphere, then taken out, ground, and passed through a 100-mesh sieve to obtain the seaweed biochar-derived carbon material.

[0013] Preferably, after obtaining the seaweed biochar-derived carbon material in step S6, a reactivation treatment step is further included, specifically comprising: The seaweed biochar-derived carbon material was added to wastewater containing dye-type organic pollutants for adsorption treatment, and the adsorbed material was obtained after solid-liquid separation. The adsorbed material was mixed with fresh aqueous treatment liquid at a ratio of 1g:15mL and then hydrothermally treated at 150℃ for 4h. After solid-liquid separation, it was washed three times with deionized water and dried at 75℃ for 12h. Subsequently, it was placed in a nitrogen atmosphere and heat-treated at 340℃ for 1h to obtain the reactivated seaweed biochar-derived carbon material.

[0014] The beneficial effects of this invention are: This invention uses the aqueous and oil phases obtained from the same batch of brown algae liquid phase products for the aqueous phase modification of sodium-based bentonite and subsequent oil phase loading, so that the surface modification of the mineral carrier and the introduction of organic components are completed continuously in the same preparation system. This is beneficial to improve the comprehensive utilization rate of the liquid phase products, improve the uniformity of oil phase loading, and reduce the loss of organic components during the water washing process. After subsequent nitrogen atmosphere heat treatment, the obtained material has a good pore structure and adsorption performance, and can be reused through reactivation treatment. Attached Figure Description

[0015] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a schematic diagram of the preparation method of seaweed biochar-derived carbon materials in Example 1; Figure 2 This is a schematic diagram illustrating the sequential utilization of the aqueous and oil phases in the same batch in Example 1. Detailed Implementation

[0017] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0018] Brown algae raw materials refer to brown algae biomass raw materials containing seaweed polysaccharides, proteins, mineral salts and oxygen-containing organic components, specifically using kelp, Sargassum or wakame seaweed, etc.

[0019] The liquid phase product is the liquid phase component obtained after brown algae powder is transformed in a closed hydrothermal environment. It includes a hydrophobic oil phase component that can be extracted with ethyl acetate, as well as polar oxygen-containing components, low-molecular-weight organic acids, phenolic hydroxyl components and soluble inorganic salts that are retained in the aqueous phase.

[0020] The aqueous phase treatment solution is formed by removing residual ethyl acetate, quantitatively concentrating and acidifying the aqueous phase product; The oil phase product is a hydrophobic organic component obtained by extracting the liquid phase product from the same batch with ethyl acetate. After being diluted with ethanol, it is added dropwise to the bentonite intermediate that has been modified by the aqueous phase, so that the oil phase component is gradually loaded on the surface of the bentonite and in the interlayer pores, reducing local agglomeration and uneven loading caused by direct mixing.

[0021] The aqueous and oil phase products were derived from the same batch of brown algae liquid phase products and were used in the order of first modifying the aqueous phase and then loading the oil phase. Heat treatment in a nitrogen atmosphere at 350–400℃ can preserve the bentonite skeleton and at the same time promote the transformation of seaweed-derived organic components into a stable carbonaceous layer, so that the resulting material has both a mineral layered structure, oxygen-containing functional groups and carbonaceous adsorption sites. Therefore, the resulting seaweed biochar-derived carbon material can be used for the adsorption treatment of dye-based organic pollutant wastewater. Furthermore, the adsorbed material can be reactivated through hydrothermal treatment with fresh aqueous phase treatment liquid and low-temperature heat treatment, thereby improving the material's reusability.

[0022] Example 1, referring to Figure 1 and Figure 2 ; This embodiment uses brown algae as the carbon source and employs a process route of hydrothermal liquefaction, ethyl acetate extraction, aqueous phase treatment liquid modification of sodium-based bentonite, oil phase loading, and nitrogen atmosphere heat treatment. Under the conditions of hydrothermal liquefaction temperature of 295℃, aqueous phase treatment liquid pH of 4.0, oil phase product to aqueous phase modified bentonite intermediate mass ratio of 0.18:1, and heat treatment temperature of 375℃, the test results of the seaweed biochar derived carbon material obtained by the technical solution of this invention are verified when the aqueous phase product and oil phase product obtained from the same batch of liquid phase products are used sequentially for aqueous phase modification and oil phase loading. The brown algae raw material is dried kelp, and the sodium-based bentonite is industrial sodium-based bentonite that has passed through a 100-mesh sieve. Cut dried kelp into small pieces less than 2cm, wash it 4 times with deionized water, dry it in a forced-air dryer at 65℃ until the quality is constant, pulverize it and pass it through a 100-mesh sieve to obtain seaweed powder; Weigh 50g of seaweed powder, add 500g of deionized water, stir to form a suspension, then transfer to a closed reaction vessel with an effective volume of 1L, and add more deionized water to make the liquid volume of the reaction material 60% of the effective volume of the reaction vessel; Nitrogen gas was introduced into the reactor for 10 minutes before the reaction, and then the temperature was raised to 295°C under stirring at 400 r / min and held at the temperature for 45 minutes for hydrothermal liquefaction reaction. After the reaction is complete, the reactor is cooled to room temperature. After opening the reactor, the product is filtered, the filtrate is collected, and the filter cake is washed three times with deionized water. The filtrate and the filter cake washing liquid are combined to obtain the liquid phase product.

[0023] Take the above liquid product and mix it with ethyl acetate at a volume ratio of 1:2 for extraction. Each extraction is performed by shaking for 10 min and then allowed to stand for 20 min to separate the layers. The extraction is repeated 3 times in total. The organic phases obtained from the three extractions were combined, and ethyl acetate was removed under reduced pressure at 45°C to obtain the organic extract, which was used as the oil phase product. The aqueous phases obtained from the three processes were combined, and the residual organic phase in the upper layer was removed by liquid separation to obtain the aqueous phase product; the oil phase product and the aqueous phase product were obtained by separating the liquid phase product from the same batch.

[0024] The aqueous phase product was treated under reduced pressure at 45℃ for 30 min to remove residual ethyl acetate. The volume of the aqueous phase product after the removal of residual ethyl acetate was measured, and based on this volume, it was concentrated under reduced pressure to 35%. The pH was adjusted to 4.0 with 1 mol / L hydrochloric acid, and the solution was allowed to stand at 35℃ for 60 min to obtain the aqueous phase treatment solution.

[0025] Weigh 10g of sodium-based bentonite and add it to 200mL of aqueous treatment solution. Stir at 45℃ for 8 hours. During the stirring process, 1 mol / L hydrochloric acid was added to maintain the pH of the system at 4.0, so that the aqueous treatment solution could come into contact with the sodium-based bentonite. After stirring, the mixture was allowed to stand at 40°C for 24 hours, then centrifuged at 5000 r / min for 10 min for solid-liquid separation. The solid was washed three times with deionized water adjusted to pH 4.0 with hydrochloric acid to obtain an aqueous modified bentonite intermediate.

[0026] The aqueous modified bentonite intermediate was dried at 75℃ to a moisture content of 10%, pulverized and passed through a 100-mesh sieve; 10g of the aqueous modified bentonite intermediate was weighed on a dry basis, and the actual sample weight was adjusted according to the moisture content. Weigh 1.8g of the oil phase product and add it to 7.2g of ethanol to prepare an oil phase dilution solution. Add the oil phase dilution solution dropwise to the aqueous phase modified bentonite intermediate within 45min, with a stirring speed of 500r / min during the dropwise addition process. After the addition was completed, the mixture was stirred at 60°C for 60 min, and the ethanol was removed under reduced pressure at 60°C to obtain the oil-phase supported composite precursor. The mass ratio of the oil-phase product to the aqueous-phase modified bentonite intermediate was 0.18:1, based on the dry basis mass of the aqueous-phase modified bentonite intermediate.

[0027] The oil-supported composite precursor was placed in a tube furnace and heated to 375℃ at 3℃ / min under a nitrogen atmosphere of 150mL / min and held for 1.5h. After the heat preservation is completed, nitrogen gas is continuously introduced to cool the furnace temperature to below 80°C. After being taken out, it is ground and passed through a 100-mesh sieve to obtain kelp-based seaweed biochar-derived carbon material.

[0028] To evaluate the impact of various process conditions on material properties, controls 1-1 to 1-5 were set up. All controls used the same batch of raw materials and intermediate products. Except for the differences listed in Table 1, the other preparation conditions, detection methods and calculation methods were the same as in Example 1. Reference 1-1 is the original sodium-based bentonite, while industrial sodium-based bentonite that has passed through a 100-mesh sieve is used directly.

[0029] References 1-2 are aqueous phase modified materials only. Their preparation method is as follows: sodium-based bentonite is treated according to the aqueous phase modification steps in this embodiment. The resulting solid is dried at 75°C to a moisture content of 10%, pulverized and passed through a 100-mesh sieve, and then directly treated under the nitrogen heat treatment conditions of this embodiment without oil phase loading.

[0030] References 1-3 are oil-phase-only loaded materials; their preparation method is as follows: without aqueous phase modification, 1.8g of oil phase product is added to 7.2g of ethanol to form an oil phase dilution, which is then added dropwise to 10g of original sodium-based bentonite on a dry basis within 45min. The stirring speed during the dropwise addition process is 500r / min. After the addition was completed, stirring was continued at 60°C for 60 min, and ethanol was removed under reduced pressure at 60°C. Then, the mixture was treated under nitrogen heat treatment conditions as described in this embodiment.

[0031] References 1-4 are materials that are first loaded with oil phase and then treated with aqueous phase; their preparation method is as follows: first, the oil phase product is loaded onto the original sodium-based bentonite according to the method of References 1-3 and the ethanol is removed to obtain oil phase loaded bentonite; The obtained oil-phase loaded bentonite is then added to the aqueous phase treatment solution and processed, aged, centrifuged, washed, dried and sieved according to the aqueous phase modification steps in this embodiment. Subsequently, it is treated according to the nitrogen heat treatment conditions in this embodiment.

[0032] Comparisons 1-5 represent different batches of aqueous and oil phase materials; their preparation methods are as follows: aqueous phase treatment liquid is prepared using the aqueous phase product obtained from the separation of the liquid phase product of batch A kelp, and sodium-based bentonite is modified in aqueous phase; oil phase loading is performed using the oil phase product obtained from the separation of the liquid phase product of batch B kelp. Except that the aqueous and oil products are from different batches, the other steps and parameters are the same as in this embodiment.

[0033] The obtained materials were subjected to the following tests.

[0034] Specific surface area and total pore volume were determined by nitrogen adsorption method; Before testing, the sample was degassed under vacuum at 120°C for 6 hours; The carbon content was determined using an elemental analyzer.

[0035] The amount of TOC dissolved after washing was determined as follows: 0.50 g of sample was weighed, added to 100 mL of deionized water, shaken at 25 °C for 2 h, filtered through a 0.45 μm filter membrane, and the total organic carbon concentration of the filtrate was determined.

[0036] The adsorption performance of methylene blue was determined by the following method: Prepare an aqueous solution of methylene blue with an initial concentration of 100 mg / L, weigh 0.100 g of sample and add it to 200 mL of the aqueous solution of methylene blue to make the material dosage 0.5 g / L, and shake and adsorb at 25 °C for 120 min; After adsorption, centrifuge to separate the methylene blue and measure the concentration of methylene blue in the supernatant.

[0037] The cyclic adsorption test was conducted as follows: each cycle included adsorption, solid-liquid separation, washing with deionized water, drying at 75℃ for 12 h, and re-adsorption; each adsorption used 100 mg / L methylene blue aqueous solution, the material dosage was 0.5 g / L, the adsorption temperature was 25℃, and the adsorption time was 120 min. The adsorption retention rate η3 in the third cycle is calculated according to the following formula: η3 = q3 / q1 × 100%; In the formula, q1 is the adsorption amount after the first adsorption for 120 min, and q3 is the adsorption amount after the third cycle adsorption for 120 min.

[0038] The reactivation test was conducted as follows: The material after the initial adsorption was collected by centrifugation, washed three times with deionized water, and dried at 75°C for 12 hours to obtain the adsorbed material. The adsorbed material was mixed with fresh aqueous treatment solution at a ratio of 1 g: 15 mL, and hydrothermally treated at 150°C for 4 hours. After solid-liquid separation, the material was washed three times with deionized water and dried at 75°C for 12 hours. Subsequently, it was heat-treated at 340°C for 1 hour in a nitrogen atmosphere to obtain the reactivated material. The fresh aqueous phase treatment solution is prepared by extracting the kelp liquid phase product with ethyl acetate, removing residual ethyl acetate, concentrating it to 35% of the volume after removing residual ethyl acetate, and adjusting the pH to 4.0 with hydrochloric acid. It is not treated with sodium bentonite. After reactivation, the material was tested again according to the above-mentioned methylene blue adsorption performance test method; the adsorption retention rate ηr after reactivation was calculated according to the following formula: ηr = qr / q1 × 100%; In the formula, qr is the adsorption amount of the material after 120 min of reactivation, and q1 is the adsorption amount of the corresponding sample after 120 min of initial adsorption.

[0039] Material yield is calculated as follows: For samples loaded with oil phase, the material yield is the percentage of the sum of the final dried material mass and the dry basis mass of the added sodium-based bentonite and the mass of the added oil phase product; for materials modified only by aqueous phase, the material yield is the percentage of the final dried material mass and the dry basis mass of the added sodium-based bentonite; the original sodium-based bentonite has not undergone the preparation process, and the material yield is recorded as inapplicable.

[0040] Table 1: Test results of Example 1 and control samples Table 1 records that, under the same test conditions, the specific surface area of ​​the material obtained in Example 1 was 286.4 m² / g, and the total pore volume was 0.342 cm³ / g, both of which were higher than those of the control samples. The carbon content of the material obtained in Example 1 was 24.7 wt%, which was higher than that of Control 1-2 (9.8 wt%), and also higher than that of Control 1-3 (21.5 wt%), Control 1-4 (18.9 wt%), and Control 1-5 (22.8 wt%).

[0041] In the TOC leaching test after water washing, the TOC leaching of the material obtained in Example 1 was 8.6 mg / L; the TOC leaching of controls 1-3, 1-4 and 1-5 were 24.5 mg / L, 31.2 mg / L and 16.9 mg / L, respectively; the above data correspond to the organic carbon leaching levels of materials obtained under different preparation sequences and different batch source conditions after water washing.

[0042] Under the conditions of 100 mg / L methylene blue aqueous solution, material dosage of 0.5 g / L, and adsorption at 25°C for 120 min, the adsorption capacity of the material obtained in Example 1 was 162.8 mg / g after 120 min, and the dye removal rate was 81.4% after 120 min. Under the same conditions, the adsorption capacities at 120 min for controls 1-1 to 1-5 were 48.6 mg / g, 83.4 mg / g, 121.7 mg / g, 105.3 mg / g, and 136.4 mg / g, respectively, and the dye removal rates at 120 min were 24.3%, 41.7%, 60.9%, 52.7%, and 68.2%, respectively. The dye removal rate at 120 min was calculated according to Rt=(C0-Ct) / C0×100%, which corresponds to the adsorption capacities at 120 min, qt=(C0-Ct)×V / m.

[0043] In the cyclic adsorption test, the adsorption capacity of the material obtained in Example 1 in the third cycle was 141.5 mg / g, and the adsorption capacity retention rate in the third cycle was 86.9%; the adsorption capacity retention rates in the third cycle of Controls 1-1 to Controls 1-5 were 52.3%, 64.8%, 71.4%, 66.1% and 76.8%, respectively.

[0044] In the reactivation test, the adsorption capacity of the material obtained in Example 1 after reactivation was 151.2 mg / g, and the adsorption capacity retention rate after reactivation was 92.9%. The adsorption capacities of controls 1-1 to 1-5 after reactivation were 28.5 mg / g, 59.4 mg / g, 96.8 mg / g, 78.0 mg / g and 119.6 mg / g, respectively, and the adsorption capacity retention rates after reactivation were 58.6%, 71.2%, 79.5%, 74.1% and 87.7%, respectively.

[0045] In this embodiment, kelp was used as the brown algae raw material, and kelp-based seaweed biochar-derived carbon materials were obtained under the following intermediate conditions: hydrothermal liquefaction temperature of 295℃, pH of aqueous phase treatment solution of 4.0, mass ratio of oil phase product to aqueous phase modified bentonite intermediate of 0.18:1, and nitrogen heat treatment temperature of 375℃.

[0046] Example 2; In this embodiment, brown algae raw material is used as carbon source. Under the lower limit parameter conditions of hydrothermal liquefaction temperature of 280℃, pH of aqueous phase treatment liquid of 3.5, mass ratio of oil phase product to aqueous phase modified bentonite intermediate of 0.10∶1, and heat treatment temperature of 350℃, the test results of seaweed biochar derived carbon material obtained by the technical solution of the present invention under low parameter combination conditions are verified. In this embodiment, dried kelp was used as brown algae raw material to prepare seaweed biochar-derived carbon materials under the following conditions: hydrothermal liquefaction temperature of 280℃, pH of aqueous phase treatment solution of 3.5, mass ratio of oil phase product to aqueous phase modified bentonite intermediate of 0.10:1, and nitrogen heat treatment temperature of 350℃. Except for the process parameters explicitly described in this embodiment, the kelp washing, drying, crushing, sieving, number of ethyl acetate extractions, centrifugation conditions, oil phase dilution droplet addition time, ethanol removal conditions, nitrogen flow rate, heating rate, cooling and sieving conditions are all the same as in Example 1.

[0047] Dried kelp was washed four times with deionized water, dried at 65°C, pulverized, and passed through a 100-mesh sieve to obtain seaweed powder. 50g of seaweed powder was weighed and added to 500g of deionized water, then stirred to form a suspension. The volume of the suspension was measured to be 540 mL beforehand. It was then transferred into a closed reaction vessel with an effective volume of 900 mL, so that the liquid volume of the reactants was 60% of the effective volume of the reaction vessel. Nitrogen gas was introduced into the reactor for 10 minutes before the reaction, and then the temperature was raised to 280°C under stirring at 400 r / min and kept at the temperature for 45 minutes for hydrothermal liquefaction reaction. After the reaction was completed, the reactor was cooled to room temperature, the hydrothermal liquefaction reaction product was filtered, the filtrate was collected, and the filter cake was washed three times with deionized water. The filtrate and filter cake washing liquid were combined to obtain the liquid phase product.

[0048] The above liquid product was mixed with ethyl acetate at a volume ratio of 1:2 and extracted. Each extraction was performed by shaking for 10 min and then allowed to stand for 20 min to separate the layers. The extraction was repeated 3 times in total. The organic phases obtained from the three extractions were combined, and ethyl acetate was removed under reduced pressure at 45°C to obtain the organic extract product, which was used as the oil phase product. The aqueous phases obtained from the three extractions were combined, and the residual organic phase in the upper layer was removed by separation to obtain the aqueous phase product; the oil phase product and the aqueous phase product were obtained by separating the liquid phase product from the same batch.

[0049] The aqueous phase product was treated under reduced pressure at 45℃ for 30 min to remove residual ethyl acetate; the volume of the aqueous phase product after the removal of residual ethyl acetate was measured, and based on this volume, it was concentrated under reduced pressure to 35%, the pH was adjusted to 3.5 with 1 mol / L hydrochloric acid, and the solution was allowed to stand at 35℃ for 60 min to obtain the aqueous phase treatment solution. The aqueous phase treatment liquid described in this embodiment refers to the treatment liquid formed after removing residual ethyl acetate, concentrating and acidifying the aqueous phase product. It can be used for the aqueous phase modification of sodium-based bentonite, and can also be used as a source of fresh aqueous phase treatment liquid for reactivation treatment.

[0050] Weigh 10g of sodium-based bentonite and add it to 200mL of the above aqueous treatment solution. Stir at 45℃ for 8 hours. During stirring, add 1mol / L hydrochloric acid to maintain the pH of the system at 3.5. After stirring, the mixture was allowed to stand at 40°C for 24 hours, then centrifuged at 5000 r / min for 10 min for solid-liquid separation. The solid was washed three times with deionized water adjusted to pH 3.5 with hydrochloric acid to obtain an aqueous modified bentonite intermediate.

[0051] The aqueous-phase modified bentonite intermediate was dried at 75℃ to a moisture content of 10%, pulverized, and passed through a 100-mesh sieve. 11.11 g of the aqueous-phase modified bentonite intermediate on a wet basis was weighed, corresponding to a dry basis mass of 10.0 g. 1.0 g of the oil phase product was weighed and added to 4.0 g of ethanol to prepare a diluted oil phase solution. The oil phase dilution was added dropwise to the above aqueous phase modified bentonite intermediate within 45 min, and the stirring speed during the dropwise addition process was 500 r / min; After the addition was completed, the mixture was stirred at 60°C for 60 min, and the ethanol was removed under reduced pressure at 60°C to obtain the oil-phase supported composite precursor. The mass ratio of the oil-phase product to the aqueous-phase modified bentonite intermediate was 0.10:1, based on the dry basis mass of the aqueous-phase modified bentonite intermediate.

[0052] The oil-supported composite precursor was placed in a tube furnace and heated to 350℃ at 3℃ / min under a nitrogen atmosphere of 150mL / min and held for 1.5h. After the heat preservation is completed, nitrogen gas is continuously introduced to cool the furnace temperature to below 80°C. After being taken out, it is ground and passed through a 100-mesh sieve to obtain kelp-based seaweed biochar-derived carbon material.

[0053] To evaluate the impact of various process parameters on material properties, controls 2-1 to 2-5 were set up. All controls used the same batch of raw materials and intermediate products. Except for the differences listed in Table 2, the other preparation conditions, detection methods and calculation methods were the same as in Example 2. Reference 2-1 is the original sodium-based bentonite, and industrial sodium-based bentonite that has passed through a 100-mesh sieve is used.

[0054] Reference 2-2 is a water-phase modified material. Its preparation method is as follows: sodium-based bentonite is treated according to the water-phase modification steps of this embodiment. After aging, centrifugation, washing, drying and sieving, the resulting solid is directly treated according to the nitrogen heat treatment conditions of this embodiment without oil phase loading.

[0055] References 2-3 are oil-phase-only loaded materials, prepared as follows: without aqueous phase modification, 1.0 g of oil phase product is added to 4.0 g of ethanol to form an oil phase dilution, and then added dropwise to 10.0 g of original sodium-based bentonite within 45 min; after the dropwise addition is completed, stirring is continued at 60 °C for 60 min, and ethanol is removed under reduced pressure at 60 °C, followed by nitrogen heat treatment according to the conditions of this embodiment.

[0056] Reference 2-4 is a material that is first loaded with oil phase and then treated with aqueous phase. Its preparation method is as follows: first, the oil phase product is loaded onto the original sodium-based bentonite according to the method of Reference 2-3 and the ethanol is removed to obtain oil phase loaded bentonite; then the obtained oil phase loaded bentonite is added to the aqueous phase treatment liquid of this embodiment, and treated according to the aqueous phase modification, aging, centrifugation, washing, drying and sieving steps of this embodiment, and then treated according to the nitrogen heat treatment conditions of this embodiment.

[0057] Comparisons 2-5 are materials prepared from different batches of aqueous and oil phase products. The preparation methods are as follows: aqueous phase treatment liquid is prepared using the aqueous phase product obtained from the separation of the liquid phase product of kelp in batch A, and sodium-based bentonite is modified in aqueous phase; oil phase loading is performed using the oil phase product obtained from the separation of the liquid phase product of kelp in batch B. Except that the aqueous and oil products are from different batches, the other steps and parameters are the same as in this embodiment.

[0058] The structural parameters and adsorption performance of the obtained material were tested; the specific surface area and total pore volume were determined by nitrogen adsorption-desorption method. Before the test, the sample was degassed under vacuum at 120℃ for 6 h; the carbon content was determined by elemental analyzer; the TOC dissolution after water washing was determined by the following method: 0.50 g of sample was weighed, added to 100 mL of deionized water, shaken at 25℃ for 2 h, filtered through a 0.45 μm filter membrane, and the total organic carbon concentration of the filtrate was determined.

[0059] The adsorption performance of methylene blue was determined as follows: An initial concentration of 100 mg / L methylene blue aqueous solution was prepared. 0.100 g of sample was weighed and added to 200 mL of the methylene blue aqueous solution, making the total material dosage 0.5 g / L. The solution was shaken and adsorbed at 25 °C for 120 min. After adsorption, the solution was centrifuged, and the concentration of methylene blue in the supernatant was measured. The adsorption capacity qt and removal rate Rt after 120 min were calculated using the following formulas: qt = (C0 - Ct) × V / m; Rt = (C0 - Ct) / C0 × 100%; In the formula, C0 is the initial concentration of methylene blue in mg / L; Ct is the concentration of methylene blue after 120 min of adsorption in mg / L; V is the volume of the methylene blue aqueous solution in L; and m is the sample mass in g.

[0060] In the cyclic adsorption experiment, each cycle included adsorption, solid-liquid separation, deionized water washing, drying at 75℃ for 12 h, and re-adsorption. Each adsorption cycle used a 100 mg / L methylene blue aqueous solution, with a material dosage of 0.5 g / L, an adsorption temperature of 25℃, and an adsorption time of 120 min. The adsorption capacity retention rate η3 in the third cycle was calculated using the following formula: η3 = q3 / q1 × 100%; In the formula, q1 is the adsorption amount after the first adsorption for 120 min, and q3 is the adsorption amount after the third cycle adsorption for 120 min.

[0061] In the reactivation experiment, the material after the first adsorption was collected by centrifugation, washed three times with deionized water, and dried at 75℃ for 12h to obtain the adsorbed material. The adsorbed material was mixed with fresh aqueous treatment solution at a ratio of 1g:15mL and hydrothermally treated at 150℃ for 4h. After solid-liquid separation, it was washed three times with deionized water and dried at 75℃ for 12h. Subsequently, it was placed in a nitrogen atmosphere and heat-treated at 340℃ for 1h to obtain the reactivated material. The fresh aqueous phase treatment solution was prepared by extracting the kelp liquid phase product with ethyl acetate, removing residual ethyl acetate, concentrating to 35% of the volume after removing residual ethyl acetate, and adjusting the pH to 4.0 with hydrochloric acid. It was not treated with sodium bentonite. The reactivated material was tested again according to the above-mentioned methylene blue adsorption performance test method; the adsorption retention rate ηr after reactivation was calculated according to the following formula: ηr = qr / q1 × 100%; In the formula, qr is the adsorption amount of the material after 120 min of reactivation, and q1 is the adsorption amount of the corresponding sample after 120 min of initial adsorption.

[0062] Material yield is calculated as follows: For samples loaded with oil phase, the material yield is the percentage of the sum of the final dried material mass and the dry basis mass of the added sodium-based bentonite and the mass of the added oil phase product; for materials modified only by aqueous phase, the material yield is the percentage of the final dried material mass and the dry basis mass of the added sodium-based bentonite; the original sodium-based bentonite has not undergone the preparation process, and the material yield is recorded as inapplicable.

[0063] Table 2: Structural parameters and adsorption performance test results of the materials obtained in Example 2 and the control materials In Table 2, the specific surface area of ​​the material obtained in Example 2 was 248.7 m² / g, and the total pore volume was 0.301 cm³ / g; the specific surface areas of Controls 2-1, 2-2, 2-3, 2-4, and 2-5 were 71.8 m² / g, 116.4 m² / g, 178.9 m² / g, 159.6 m² / g, and 205.3 m² / g, respectively, and the total pore volumes were 0.096 cm³ / g, 0.137 cm³ / g, 0.211 cm³ / g, 0.193 cm³ / g, and 0.249 cm³ / g, respectively.

[0064] The carbon content of the material obtained in Example 2 was 20.8 wt%, and the TOC leaching amount after water washing was 9.4 mg / L; the carbon content of the oil-phase-supported material in Controls 2-3 was 18.6 wt%, and the TOC leaching amount after water washing was 22.8 mg / L; the carbon content of the oil-phase-supported material in Controls 2-4 was 16.9 wt%, and the TOC leaching amount after water washing was 28.6 mg / L; the carbon content of the materials prepared from different batches of aqueous and oil-phase products in Controls 2-5 was 19.4 wt%, and the TOC leaching amount after water washing was 15.7 mg / L.

[0065] Under the conditions of 100 mg / L methylene blue aqueous solution, material dosage of 0.5 g / L, and adsorption at 25°C for 120 min, the adsorption capacity of the material obtained in Example 2 was 153.6 mg / g at 120 min, and the dye removal rate at 120 min was 76.8%. The adsorption capacities at 120 min for controls 2-1 to 2-5 were 48.6 mg / g, 73.2 mg / g, 104.8 mg / g, 92.4 mg / g, and 119.6 mg / g, respectively, and the dye removal rates at 120 min were 24.3%, 36.6%, 52.4%, 46.2%, and 59.8%, respectively; wherein, the adsorption capacity and dye removal rate at 120 min were calculated based on the same set of adsorption test data.

[0066] In the cyclic adsorption test, the adsorption capacity of the material obtained in Example 2 in the third cycle was 127.2 mg / g, and the adsorption capacity retention rate in the third cycle was 82.8%. The adsorption capacities in the third cycles of Controls 2-1 to Controls 2-5 were 25.4 mg / g, 45.9 mg / g, 72.3 mg / g, 58.8 mg / g and 90.1 mg / g, respectively, and the adsorption capacity retention rates in the third cycle were 52.3%, 62.7%, 69.0%, 63.6% and 75.3%, respectively.

[0067] In the reactivation test, the reactivated adsorption capacity of the material obtained in Example 2 was 139.4 mg / g, and the adsorption capacity retention rate after reactivation was 90.8%. The reactivated adsorption capacities of controls 2-1 to 2-5 were 28.5 mg / g, 50.8 mg / g, 81.9 mg / g, 66.7 mg / g and 101.3 mg / g, respectively, and the adsorption capacity retention rates after reactivation were 58.6%, 69.4%, 78.1%, 72.2% and 84.7%, respectively.

[0068] In this embodiment, under the conditions of kelp raw material, hydrothermal liquefaction temperature of 280℃, pH of aqueous treatment solution of 3.5, mass ratio of oil phase product to aqueous modified bentonite intermediate of 0.10:1, and nitrogen heat treatment temperature of 350℃, kelp-based seaweed biochar derived carbon material was obtained. Table 2 lists the test results of this material and each control material in terms of structural parameters, TOC leaching after water washing, methylene blue adsorption performance, cyclic adsorption performance and reactivation performance.

[0069] Example 3; This embodiment uses brown algae as the carbon source. Under the upper limit parameters of hydrothermal liquefaction temperature of 310℃, pH of aqueous treatment solution of 4.5, mass ratio of oil phase product to aqueous modified bentonite intermediate of 0.25:1, and heat treatment temperature of 400℃, the test results of seaweed biochar-derived carbon material obtained by the technical solution of the present invention under high parameter combination conditions are verified. This embodiment uses dried kelp of the same variety and pretreatment specifications as in Example 1 as the brown algae raw material. Except for the process conditions explicitly described in this embodiment, the washing, drying, and pulverizing conditions of the kelp raw material, the preparation method and liquid ratio of the reactants, the nitrogen replacement and stirring conditions before hydrothermal liquefaction, the filtration and cake washing methods of the liquid phase product, the number and ratio of ethyl acetate extraction, the reduced pressure treatment and concentration ratio of the aqueous phase product, the dosage ratio, stirring temperature and time, aging conditions, centrifugation conditions, the dropping time and stirring conditions of the oil phase dilution, the ethanol removal conditions, and the nitrogen flow rate, heating rate, holding time, cooling, and sieving conditions are all the same as in Example 1.

[0070] Weigh 50g of seaweed powder and mix it with 500g of deionized water to form a reaction mixture. Add the reaction mixture to a sealed reaction vessel with an effective volume of 900mL, filling the vessel to 60% of its effective volume. After nitrogen purging, the temperature was raised to 310°C under stirring at 400 rpm and maintained for 45 min. After the reaction was completed, the mixture was cooled to room temperature, filtered and washed with the filter cake according to the method described in Example 1, and the filtrate and filter cake washing liquid were combined to obtain the liquid product.

[0071] The liquid product was extracted three times with ethyl acetate according to the extraction method described in Example 1. The organic phases obtained from the three extractions were combined, and ethyl acetate was removed under reduced pressure to obtain the oil phase product; the aqueous phases obtained from the three extractions were combined and the residual organic phase was removed to obtain the aqueous phase product. The oil phase product and the aqueous phase product are obtained by separating the liquid phase product from the same hydrothermal liquefaction reaction in the same reactor.

[0072] The aqueous phase product was subjected to vacuum treatment to remove residual ethyl acetate. Based on the volume of the aqueous phase product after removal of residual ethyl acetate, it was concentrated under vacuum to 35% of that volume. The pH was adjusted to 4.5 using 1 mol / L hydrochloric acid, and the solution was allowed to stand at 35°C for 60 min to obtain the aqueous phase treatment solution.

[0073] Weigh 10.0 g of sodium-based bentonite and add it to 200 mL of aqueous treatment solution. Stir at 45 °C for 8 h. During stirring, add 1 mol / L hydrochloric acid to maintain the pH of the system at 4.5. After stirring, the mixture was allowed to stand at 40°C for 24 hours and then centrifuged at 5000 r / min for 10 min for solid-liquid separation. The solid was washed three times with deionized water adjusted to pH 4.5 with hydrochloric acid to obtain an aqueous modified bentonite intermediate.

[0074] The aqueous-phase modified bentonite intermediate was dried at 75℃ to a moisture content of 10%, pulverized, and passed through a 100-mesh sieve. 11.11 g of the aqueous-phase modified bentonite intermediate (wet basis) was weighed, corresponding to a dry basis mass of 10.0 g. 2.50 g of the oil phase product was weighed and added to 10.0 g of ethanol to prepare an oil phase dilution solution. The mass ratio of the oil phase product to ethanol was 1:4. The dry basis mass ratio of the oil phase product to the aqueous-phase modified bentonite intermediate was 0.25:1.

[0075] Under stirring conditions of 500 r / min, the oil phase dilution was added dropwise to the aqueous phase modified bentonite intermediate within 45 min; After the addition was completed, the mixture was stirred at 60°C for 60 min, and then the ethanol was removed under reduced pressure at 60°C to obtain the oil-supported composite precursor.

[0076] The oil-supported composite precursor was placed in a tube furnace, nitrogen gas was introduced at a flow rate of 150 mL / min, the temperature was increased to 400℃ at a heating rate of 3℃ / min and held for 1.5 h. After the heat preservation is completed, nitrogen gas is continuously introduced. When the temperature inside the furnace drops below 80°C, the material is taken out, ground, and passed through a 100-mesh sieve to obtain the kelp-based seaweed biochar derived carbon material of Example 3.

[0077] To evaluate the impact of each process action on material properties under the upper limit parameter combination, controls 3-1 to 3-5 were set up; All controls used the same batch of raw materials and intermediate products. Except for the differences listed in Table 3, the other preparation conditions, detection methods and calculation methods were the same as in Example 3. Control 3-1 is the original sodium-based bentonite, and its pretreatment and sieving conditions are the same as those in Example 1.

[0078] Reference 3-2 is a material modified only in the aqueous phase; An aqueous treatment solution was prepared using the aqueous product obtained under hydrothermal liquefaction conditions at 310°C in this embodiment. The pH of the aqueous treatment solution was adjusted and maintained at 4.5. Sodium-based bentonite was treated according to the aqueous modification conditions of this embodiment without oil phase loading, and then heat-treated at 400°C under a nitrogen atmosphere.

[0079] Reference 3-3 is an oil-phase-only loaded material; the oil phase product is loaded onto the original sodium-based bentonite, and the dry basis mass ratio of the oil phase product to the original sodium-based bentonite is 0.25:1. The loading and ethanol removal conditions are the same as in this example, and then heat treatment is carried out at 400°C in a nitrogen atmosphere.

[0080] Comparison 3-4 shows materials that were first loaded with the oil phase and then treated with the aqueous phase; First, the oil phase product was loaded onto the original sodium-based bentonite, with a dry weight ratio of 0.25:1 between the oil phase product and the original sodium-based bentonite. Then, the bentonite loaded with oil phase was added to an aqueous treatment solution with a pH of 4.5 and treated according to the stirring, aging, centrifugation, washing and drying conditions of this embodiment. Subsequently, it was heat-treated at 400°C under a nitrogen atmosphere.

[0081] Comparisons 3-5 show materials prepared from different batches of aqueous and oil phase products; Both batches A and B use kelp powder from the same source and with the same pretreatment specifications. The kelp powder feeding quality, the mass ratio of kelp powder to water, the reactor specifications, the liquid filling ratio, the nitrogen purging time, the stirring speed, the hydrothermal liquefaction temperature, the reaction time, the filtration method, and the ethyl acetate extraction conditions are all the same as in this embodiment. Batch A and batch B were fed and hydrothermally liquefied independently. The aqueous phase product obtained from the separation of the liquid phase product of batch A was used to prepare the aqueous phase treatment liquid, and the oil phase product obtained from the separation of the liquid phase product of batch B was used for oil phase loading. The remaining operating conditions were the same as in this embodiment.

[0082] The specific surface area, total pore volume, carbon content, TOC leaching amount after water washing, methylene blue adsorption amount, dye removal rate, cyclic adsorption performance and reactivation performance of each material were determined according to the test methods and calculation formulas described in Example 1. The methylene blue adsorption test used an aqueous solution of methylene blue with an initial concentration of 100 mg / L, a material dosage of 0.5 g / L, an adsorption temperature of 25 °C, and an adsorption time of 120 min.

[0083] The material yield was calculated according to the formula described in Example 1; for materials with oil phase loading, the feed mass basis was the sum of the dry basis mass of sodium bentonite and the mass of the oil phase product; for materials modified only by the aqueous phase, the feed mass basis was the dry basis mass of sodium bentonite; the original sodium bentonite had not undergone the material preparation process and was not included in the material yield calculation.

[0084] Table 3: Structural parameters and adsorption properties of the materials obtained in Example 3 and the control materials In Table 3, the specific surface area of ​​the material obtained in Example 3 was 140.4 m² / g, 53.8 m² / g, 85.2 m² / g, and 31.9 m² / g higher than that of Controls 3-2, 3-3, 3-4, and 3-5, respectively.

[0085] The differences in TOC dissolution between the material obtained in Example 3 and Controls 3-3, 3-4 and 3-5 were 16.3 mg / L, 22.9 mg / L and 8.2 mg / L, respectively.

[0086] Under the test conditions of an initial methylene blue concentration of 100 mg / L, a material dosage of 0.5 g / L, an adsorption temperature of 25 °C, and an adsorption time of 120 min, the methylene blue adsorption capacity of the material obtained in Example 3 was 158.4 mg / g, and the methylene blue removal rate was 79.2%. The methylene blue adsorption capacities of controls 3-1 to 3-5 were 48.6 mg / g, 80.2 mg / g, 116.8 mg / g, 99.4 mg / g, and 130.2 mg / g, respectively, and the methylene blue removal rates were 24.3%, 40.1%, 58.4%, 49.7%, and 65.1%, respectively.

[0087] Compared with the aqueous phase-modified material, the methylene blue adsorption capacity of the material obtained in Example 3 increased by 78.2 mg / g in 120 min; compared with the oil phase-loaded material, it increased by 41.6 mg / g; compared with the material first loaded in the oil phase and then treated in the aqueous phase, it increased by 59.0 mg / g; and compared with the materials prepared from different batches of aqueous phase products and oil phase products, it increased by 28.2 mg / g.

[0088] In the third cycle adsorption test, compared with the controls 3-5, the material obtained in Example 3 showed an increase of 34.8 mg / g in adsorption capacity and an increase of 8.3 percentage points in adsorption capacity retention rate.

[0089] In the reactivation test, compared with the controls 3-5, the adsorption capacity of the material obtained in Example 3 increased by 32.7 mg / g after reactivation, and the adsorption capacity retention rate increased by 5.1 percentage points after reactivation.

[0090] Example 3 uses a hydrothermal liquefaction temperature of 310℃, an aqueous phase treatment condition of pH 4.5, a dry basis mass ratio of 0.25:1 between the oil phase product and the aqueous phase modified bentonite intermediate, and a nitrogen heat treatment temperature of 400℃ to complete the material preparation.

[0091] Example 4; In this embodiment, different brown algae raw materials were used to verify the test results of the seaweed biochar-derived carbon materials obtained by the technical solution of the present invention under the same conditions of hydrothermal liquefaction, phase separation, aqueous phase modification, oil phase loading and heat treatment. In this embodiment, Sargassum fusiforme replaces the kelp raw material of equal dry basis in Example 1; the hydrothermal liquefaction temperature is 295℃, the pH of the system in the aqueous phase treatment liquid and aqueous phase modification process is 4.0, the dry basis mass ratio of the oil phase product to the aqueous phase modified bentonite intermediate is 0.18:1, and the nitrogen atmosphere heat treatment temperature is 375℃. Except for the types of raw materials and the specific conditions clearly described in this embodiment, the raw material pretreatment, reactant preparation, hydrothermal liquefaction, liquid phase product separation, ethyl acetate extraction, aqueous phase treatment, bentonite modification, oil phase dropwise loading, heat treatment, and cooling sieving methods are all the same as in Example 1.

[0092] Take dried Sargassum from the same source batch, wash it 4 times with deionized water, dry it at 65℃, pulverize it and pass it through a 100-mesh sieve to obtain Sargassum powder. Weigh 100.0g of Sargassum powder, add 1000.0g of deionized water, and stir to form a reaction mixture. The volume of the reaction mixture was measured to be 1.08L. Transfer it to a closed reaction vessel with an effective volume of 1.80L. The liquid volume of the reaction mixture is 60% of the effective volume of the reaction vessel.

[0093] Nitrogen gas was introduced into the sealed reactor for 10 minutes, and the temperature was raised to 295°C under stirring at 400 r / min. The hydrothermal liquefaction reaction was carried out for 45 minutes. After the reaction was completed, the mixture was cooled to room temperature, the reaction product was filtered, the filtrate was collected, and the filter cake was washed three times with deionized water. The filtrate and the filter cake washing liquid were combined to obtain 1.25 L of liquid product.

[0094] The liquid product was extracted with ethyl acetate at a volume ratio of 1:2, using 2.50 L of ethyl acetate each time, for a total of 3 extractions. The organic phases obtained from the three extractions were combined, and ethyl acetate was removed under reduced pressure at 45°C to obtain 13.6 g of oil phase product. The aqueous phases obtained from the three extractions were combined, and the residual organic phase was removed by liquid separation to obtain aqueous phase product. Both the oil phase product and the aqueous phase product were obtained by separating the liquid phase product obtained from the same feeding, the same reaction vessel, and the same hydrothermal liquefaction reaction.

[0095] The aqueous product was treated under reduced pressure at 45°C for 30 min to remove residual ethyl acetate. The volume of the treated aqueous product was 1.10 L. It was concentrated under reduced pressure to 385 mL, the pH was adjusted to 4.0 with 1 mol / L hydrochloric acid, and the solution was allowed to stand at 35°C for 60 min to obtain the aqueous treatment solution.

[0096] Weigh 10.0 g of sodium-based bentonite and add it to 200 mL of aqueous treatment solution. Stir at 45 °C for 8 h. During stirring, add 1 mol / L hydrochloric acid to maintain the pH of the system at 4.0. After stirring, the mixture was allowed to stand at 40°C for 24 hours and then centrifuged at 5000 r / min for 10 min for solid-liquid separation. The solid was washed three times with deionized water adjusted to pH 4.0 with hydrochloric acid to obtain an aqueous modified bentonite intermediate.

[0097] The aqueous modified bentonite intermediate was dried at 75℃ to a moisture content of 10%, pulverized, and passed through a 100-mesh sieve. Weigh 11.11 g of the aqueous modified bentonite intermediate on a wet basis, which corresponds to 10.0 g on a dry basis. Weigh 1.80 g of the oil phase product from the same batch and add it to 7.20 g of ethanol to prepare an oil phase dilution.

[0098] Under stirring conditions of 500 r / min, the oil phase dilution was added dropwise to the aqueous phase modified bentonite intermediate within 45 min; After the addition was completed, the mixture was stirred at 60°C for 60 min, and then the ethanol was removed under reduced pressure at 60°C to obtain the oil-supported composite precursor.

[0099] The oil-supported composite precursor was placed in a tube furnace, nitrogen gas was introduced at a flow rate of 150 mL / min, and the temperature was increased to 375℃ at a heating rate of 3℃ / min and held for 1.5 h. After the heat preservation was completed, nitrogen gas was continued to be introduced. When the temperature inside the furnace dropped to below 80°C, the material was taken out, ground and passed through a 100-mesh sieve to obtain 8.07g of Sargassum-based seaweed biochar-derived carbon material.

[0100] To evaluate the impact of differences in raw materials and processes on material properties, controls 4-1 to 4-4 were set up. Except for the differences listed in Table 4, the preparation conditions, detection methods and calculation methods of each control were the same as those in Example 4; Reference 4-1 is the original sodium-based bentonite; the sodium-based bentonite was dried and passed through a 100-mesh sieve without aqueous phase modification, oil phase loading, or nitrogen atmosphere heat treatment.

[0101] Reference 4-2 is a material modified only by the aqueous phase of Sargassum. 10.0g of sodium bentonite was modified by the aqueous phase treatment solution obtained in this embodiment. After stirring, aging, centrifugation, washing, drying and sieving, no oil phase loading was performed. The treatment was carried out directly according to the nitrogen flow rate, heating rate, heat treatment temperature and holding time of this embodiment.

[0102] Control 4-3 is an oil-phase-only material from Sargassum; without using an aqueous phase treatment solution to treat sodium-based bentonite, 1.80g of the oil phase product was added to 7.20g of ethanol to form an oil phase dilution solution, which was then added dropwise to 10.0g of the original sodium-based bentonite. The conditions for oil phase addition, ethanol removal, and nitrogen atmosphere heat treatment are the same as in this embodiment.

[0103] Comparison 4-4 shows the materials used to prepare different batches of aqueous and oil phase products from Sargassum fusiforme. Hydrothermal liquefaction reactions of Sargassum fusiforme, batch A and batch B, were performed separately. Both batches A and B used Sargassum fusiforme powder from the same source and with the same pretreatment specifications. The feed mass, powder-to-water mass ratio, reactor specifications, liquid loading ratio, nitrogen purging time, stirring speed, hydrothermal liquefaction temperature, reaction time, filtration method, type of extractant, extraction ratio, and number of extractions were all identical. The aqueous phase product obtained by separating the liquid phase product from batch A was used to prepare an aqueous phase treatment liquid, which was then used for the aqueous phase modification of sodium-based bentonite. The oil phase product obtained by separating the liquid phase product from batch B was used for oil phase loading. The remaining steps and parameters were the same as in this embodiment.

[0104] The kelp-based seaweed biochar-derived carbon material obtained in Example 1 was used as a comparative sample of raw material types. This sample was only used to compare the test data of materials obtained from kelp raw materials and Sargassum raw materials under the same intermediate process conditions, and was not used as a control material for process steps.

[0105] Weigh 1.0 g of the material from Example 4 after methylene blue adsorption treatment, wash it three times with deionized water after solid-liquid separation, and dry it at 75°C for 12 h to obtain the adsorbed material.

[0106] Another Sargassum fusiforme raw material was used to prepare a new aqueous product according to the hydrothermal liquefaction and ethyl acetate extraction conditions of this embodiment; The aqueous product was dehydrated to remove residual ethyl acetate and concentrated to 35% of its original volume. The pH was then adjusted to 4.0 using 1 mol / L hydrochloric acid to obtain a fresh aqueous treatment solution that had not been treated with sodium bentonite.

[0107] Mix 1.0 g of the adsorbed material with 15 mL of fresh aqueous treatment solution, transfer the mixture into a pressure-resistant sealed reactor, and perform hydrothermal treatment at 150 °C for 4 h. After the reaction was completed, the mixture was cooled to room temperature, separated into solid and liquid phases, washed three times with deionized water, dried at 75°C for 12 hours, and then heat-treated at 340°C for 1 hour in a nitrogen atmosphere to obtain the reactivated Sargassum-based seaweed biochar-derived carbon material.

[0108] The specific surface area and total pore volume of each material were determined by nitrogen adsorption-desorption method, and the material was degassed under vacuum at 120℃ for 6 hours before testing; the carbon content was determined by elemental analysis.

[0109] The method for testing the TOC leaching amount after water washing is as follows: Weigh 0.50g of material, add it to 100mL of deionized water, shake at 25℃ for 2h, filter it using a 0.45μm filter membrane, and determine the total organic carbon concentration of the filtrate.

[0110] The methylene blue adsorption test used an initial concentration of 100 mg / L methylene blue aqueous solution, a material dosage of 0.5 g / L, an adsorption temperature of 25℃, and an adsorption time of 120 min. The adsorption capacity, removal rate, retention rate of adsorption capacity in the third cycle, and retention rate of adsorption capacity after reactivation were all calculated according to the formulas in Example 1 above.

[0111] For materials modified only by the aqueous phase, the material yield is the percentage of the dry mass of the material obtained after heat treatment to the dry mass of the added sodium-based bentonite; the original sodium-based bentonite has not undergone the material preparation process and its material yield is not calculated.

[0112] Table 4: Structural parameters and adsorption properties of the materials obtained in Example 4 and the control materials In Table 4, the specific surface area difference between Example 4 and Control 4-2 was 140.8 m² / g, and the total pore volume difference was 0.170 cm³ / g; the specific surface area difference between Example 4 and Control 4-3 was 61.2 m² / g, and the total pore volume difference was 0.081 cm³ / g; and the specific surface area difference between Example 4 and Control 4-4 was 35.6 m² / g, and the total pore volume difference was 0.038 cm³ / g.

[0113] The difference in TOC leaching amount between Example 4 and Control 4-3 after water washing was 14.3 mg / L, and the difference in TOC leaching amount between Example 4 and Control 4-4 after water washing was 7.0 mg / L.

[0114] Under the conditions of an initial methylene blue concentration of 100 mg / L, a material dosage of 0.5 g / L, an adsorption temperature of 25 °C, and an adsorption time of 120 min, the adsorption differences between Example 4 and Controls 4-2, 4-3, and 4-4 were 82.2 mg / g, 49.8 mg / g, and 34.4 mg / g, respectively.

[0115] In the third cycle adsorption test, the difference in adsorption capacity between Example 4 and Control 4-4 was 39.3 mg / g, and the difference in adsorption capacity retention rate was 8.2 percentage points.

[0116] In the reactivation test, the difference in adsorption capacity after reactivation between Example 4 and Control 4-4 was 38.7 mg / g, and the difference in adsorption capacity retention rate after reactivation was 5.7 percentage points.

[0117] The difference in specific surface area between the Sargassum-based material in Example 4 and the kelp-based raw material in Example 1 was 3.5 m² / g, 0.006 cm³ / g, 0.4 percentage points in carbon content, and 0.6 mg / L in TOC leaching after washing. The difference in methylene blue adsorption capacity at 120 min was 2.2 mg / g, the difference in adsorption retention rate after the third cycle was 1.2 percentage points, and the difference in adsorption retention rate after reactivation was 0.5 percentage points.

[0118] This embodiment records the preparation process of Sargassum raw material under the following conditions: hydrothermal liquefaction temperature of 295℃, aqueous phase treatment condition of pH 4.0, dry basis mass ratio of oil phase product to aqueous phase modified bentonite intermediate of 0.18:1, and nitrogen heat treatment temperature of 375℃.

[0119] Example 5; Based on the baseline preparation conditions of Example 1, this embodiment analyzes the effects of changes in process conditions such as batch source of aqueous and oil phase products, implementation sequence of aqueous phase modification and oil phase loading, addition method of oil phase diluent, oil phase loading ratio and heat treatment temperature on the performance of the obtained seaweed biochar-derived carbon materials. In this embodiment, kelp was used as the brown algae raw material. The hydrothermal liquefaction temperature was 295℃, the pH of the system during the aqueous phase treatment and aqueous phase modification process was 4.0, the dry basis mass ratio of the oil phase product to the aqueous phase modified bentonite intermediate was 0.18:1, and the nitrogen atmosphere heat treatment temperature was 375℃ as the benchmark conditions. The batch sources of the aqueous phase product and the oil phase product, the implementation sequence of aqueous phase modification and oil phase loading, the addition method of the oil phase dilution, the oil phase loading ratio, and the test results of the materials obtained under different heat treatment temperatures were investigated.

[0120] To evaluate the impact of the above-mentioned changes in process conditions on material properties, controls 5-1 to 5-3 and control samples 5-4A to 5-4D were set up. Except for the differences listed in Table 5, the preparation conditions, detection methods and calculation methods of each group are the same as those of the reference sample 5-0; Each group underwent three independent preparation batches. Each independent batch involved re-weighing of raw materials, hydrothermal liquefaction, phase separation treatment, material preparation, and performance testing. Three batches of reference sample 5-0 were independently re-prepared according to the complete method of Example 1; Each group of samples was tested using the same instrument, the same batch of reagents, and under the same testing conditions.

[0121] 1. Reference sample 5-0; Weigh 50.0g of kelp powder and add 500.0g of deionized water. In a closed reaction vessel with an effective volume matching the liquid ratio, carry out a hydrothermal liquefaction reaction at 295℃ for 45min. Filter, wash the filter cake and extract with ethyl acetate according to the method of Example 1 to obtain the aqueous phase product and oil phase product obtained from the same batch of liquid phase products.

[0122] After removing residual ethyl acetate from the aqueous product, it was concentrated to 35% of the treated volume, and the pH was adjusted to 4.0 using 1 mol / L hydrochloric acid. 10.0 g of sodium-based bentonite was added to 200 mL of the aqueous treatment solution for aqueous phase modification. After aging, centrifugation, washing, drying, and sieving, the aqueous phase modified bentonite intermediate was obtained.

[0123] Weigh 10.0 g of the intermediate and 1.80 g of the oil phase product from the same batch. Add the oil phase product to 7.20 g of ethanol to prepare an oil phase dilution solution, and add it dropwise to the intermediate within 45 min. After removing the ethanol, heat-treat the obtained precursor at 375 °C for 1.5 h in a nitrogen atmosphere to obtain the reference sample 5-0.

[0124] 2. Comparison 5-1: Aqueous and oil phase products from different batches; Each independent preparation batch underwent hydrothermal liquefaction reactions, with batch A and batch B used kelp powder from the same source and with the same pretreatment specifications.

[0125] Aqueous treatment solution was prepared using the aqueous product obtained from the separation of liquid phase product A, and 10.0 g of sodium-based bentonite was modified in aqueous phase. Oil phase loading was performed using the oil product obtained from the separation of liquid phase product B. The amount of oil phase product added was 1.80 g, and the remaining steps were the same as those for reference sample 5-0.

[0126] 3. Compare with 5-2: first load the oil phase, then treat the aqueous phase; This group uses aqueous and oil phase products obtained by separating liquid phase products from the same batch.

[0127] Weigh 10.0 g of the original sodium-based bentonite. Weigh 1.80 g of the oil phase product from the same batch as the aqueous phase treatment solution in this group, add it to 7.20 g of ethanol to prepare an oil phase dilution, and add it dropwise to the original sodium-based bentonite within 45 min; After the addition was completed, stirring was continued and ethanol was removed to obtain oil-phase loaded bentonite.

[0128] The obtained oil-phase loaded bentonite was added to 200 mL of aqueous treatment solution prepared from the same batch of aqueous phase products, stirred at 45 °C for 8 h, and the pH of the system was maintained at 4.0. After aging, centrifugation, washing, drying and sieving, the sample was heat-treated at 375℃ in a nitrogen atmosphere for 1.5 hours.

[0129] 4. Refer to 5-3: Add the oil phase diluent quickly; The aqueous-phase modified bentonite intermediate was prepared according to the method of reference sample 5-0. 10.0 g of the intermediate (dry basis) was weighed, and 1.80 g of the oil phase product from the same batch was added to 7.20 g of ethanol to prepare an oil phase dilution.

[0130] Under stirring conditions of 500 r / min, all the oil phase dilution was added to the aqueous phase modified bentonite intermediate within 1 min; After the addition is complete, continue stirring at 60°C for 60 min, remove ethanol under reduced pressure, and perform nitrogen atmosphere heat treatment according to the conditions of reference sample 5-0.

[0131] 5. Control sample 5-4A: oil phase mass ratio is 0.05:1; A water-modified bentonite intermediate with a dry basis mass of 10.0 g was prepared according to the method of reference sample 5-0. 0.50 g of oil phase product was weighed and added to 2.00 g of ethanol to prepare an oil phase dilution solution; the dry basis mass ratio of oil phase product to intermediate was 0.05:1, and the remaining steps were the same as those of reference sample 5-0.

[0132] 6. Control sample 5-4B: oil phase mass ratio is 0.30:1; A water-phase modified bentonite intermediate with a dry basis mass of 10.0 g was prepared according to the method of reference sample 5-0. 3.00 g of oil phase product was weighed and added to 12.00 g of ethanol to prepare an oil phase dilution solution; the dry basis mass ratio of oil phase product to intermediate was 0.30:1, and the remaining steps were the same as those of reference sample 5-0.

[0133] 7. Control sample 5-4C: heat treatment temperature was 325℃; The oil-phase supported composite precursor was prepared according to the method of reference sample 5-0. The temperature was increased to 325℃ at 3℃ / min in a nitrogen atmosphere and held for 1.5h. The remaining steps were the same as those of reference sample 5-0.

[0134] 8. Control sample 5-4D: heat treatment temperature was 425℃; The oil-phase supported composite precursor was prepared according to the method of reference sample 5-0. The temperature was increased to 425℃ at 3℃ / min in a nitrogen atmosphere and held for 1.5h. The remaining steps were the same as those of reference sample 5-0.

[0135] The specific surface area, total pore volume, carbon content, TOC leaching after water washing, methylene blue adsorption performance, cyclic adsorption performance, and material yield of each group of samples were determined according to the method described in Example 1.

[0136] Each independent preparation batch was subjected to three parallel methylene blue adsorption tests, and the arithmetic mean of the three parallel tests was taken as the adsorption test result of that preparation batch; the data listed in Table 5 are the arithmetic mean ± sample standard deviation of the results of the three independent preparation batches. The spatial variation coefficient of carbon content was determined by the following method: each independent preparation batch was not manually mixed after ethanol removal, and samples were taken from the top, middle and bottom of the material container respectively; the samples at each location were subjected to nitrogen atmosphere heat treatment under the same conditions, and the carbon content was determined by an elemental analyzer.

[0137] The CVs listed in Table 5 are the arithmetic mean ± sample standard deviation of the CVs from three independent preparation batches.

[0138] In the reactivation performance test, the materials of each group after the first methylene blue adsorption were collected after solid-liquid separation, and fresh aqueous phase treatment liquid of the same homogenization batch was used as the reactivation medium for each group. The fresh aqueous phase treatment solution was prepared from the aqueous phase product obtained by extracting the kelp liquid phase product with ethyl acetate. After removing residual ethyl acetate, the aqueous phase product was concentrated to 35% of the treated volume. The pH was adjusted to 4.0 with hydrochloric acid and it was not treated with sodium bentonite.

[0139] The adsorbed material was mixed with fresh aqueous treatment solution at a ratio of 1 g: 15 mL and hydrothermally treated at 150 °C for 4 h in a pressure-resistant sealed reactor. After solid-liquid separation, the material was washed three times with deionized water, dried at 75 °C for 12 h, and then heat-treated at 340 °C for 1 h in a nitrogen atmosphere. The adsorption capacity of the resulting material after reactivation was determined according to the conditions of the initial adsorption test.

[0140] Table 5: Test results of materials obtained under different process conditions In Table 5, the average specific surface area of ​​reference sample 5-0 was 268.9 m² / g, and the average total pore volume was 0.325 cm³ / g. The corresponding values ​​for control 5-1 were 238.6 m² / g and 0.289 cm³ / g, respectively. The difference between the average values ​​of the two groups was 30.3 m² / g and 0.036 cm³ / g, respectively. The average TOC leaching amounts after water washing for reference sample 5-0 and control 5-1 were 9.2 mg / L and 17.5 mg / L, respectively, and the average methylene blue adsorption amounts at 120 min were 162.8 mg / g and 128.6 mg / g, respectively.

[0141] The average adsorption retention rate of the reference sample 5-0 in the third cycle was 85.5%, and the average adsorption retention rate after reactivation was 92.1%; the corresponding values ​​for control 5-1 were 76.3% and 86.9%; the above two groups correspond to the combination of aqueous phase product and oil phase product in the same batch and the combination of aqueous phase product and oil phase product in different batches, respectively.

[0142] The average adsorption capacity difference between the reference sample 5-0 and the control 5-2 was 61.8 mg / g, the average difference in the adsorption capacity retention rate after the third cycle was 21.0 percentage points, and the average difference in the adsorption capacity retention rate after reactivation was 17.3 percentage points. The two groups adopted the operation sequence of first modifying the aqueous phase and then loading the oil phase, and first loading the oil phase and then treating the aqueous phase, respectively.

[0143] The average spatial variation coefficients of carbon content for the reference sample 5-0 and control 5-3 were 0.8% and 7.0%, respectively, with a difference of 6.2 percentage points. The average TOC leaching amounts after water washing for the two groups were 9.2 mg / L and 26.8 mg / L, respectively, and the average methylene blue adsorption amounts at 120 min were 162.8 mg / g and 118.4 mg / g, respectively. The oil phase diluent was added dropwise over 45 min and rapidly over 1 min, respectively, for the two groups.

[0144] When the heat treatment temperatures were 325℃, 375℃, and 425℃, the average specific surface areas of the materials were 186.7 m² / g, 268.9 m² / g, and 244.1 m² / g, respectively. The average methylene blue adsorption capacities after 120 min were 103.4 mg / g, 162.8 mg / g, and 144.2 mg / g, respectively. The average adsorption retention rates after reactivation were 75.2%, 92.1%, and 88.3%, respectively. The sample treated at 425℃ still had an average adsorption capacity of 144.2 mg / g, and its average TOC leaching after water washing was 11.6 mg / L. The above data serve as a comparison of heat treatment temperatures outside the range.

[0145] Table 5 lists the structural parameters, TOC leaching amount, methylene blue adsorption performance, cyclic adsorption performance, reactivation performance and material yield of materials obtained under different batches and product combinations, different processing sequences, different oil phase addition methods, different oil phase mass ratios and different heat treatment temperatures.

Claims

1. A method for preparing seaweed biochar-derived carbon materials, characterized in that, Includes the following steps: S1. The brown algae raw material is washed, dried and crushed, and then subjected to hydrothermal liquefaction to separate the liquid phase product; S2. The liquid phase product is extracted and separated by organic solvent to obtain an oil phase product and an aqueous phase product; The oil phase product and the aqueous phase product are obtained by separating the liquid phase product from the same batch; S3. Remove residual organic solvent from the aqueous product, concentrate it and adjust the pH to obtain an aqueous treatment solution; S4. Sodium-based bentonite is contacted with the aqueous treatment liquid to modify the sodium-based bentonite in aqueous phase, thereby obtaining an aqueous modified bentonite intermediate. S5. The oil phase product is prepared into an oil phase dilution, and after the aqueous phase modification is completed, it is added to the aqueous phase modified bentonite intermediate so that the oil phase product is loaded on the aqueous phase modified bentonite intermediate. The solvent in the oil phase dilution solution is removed to obtain the oil phase supported composite precursor; S6. The oil-supported composite precursor is heat-treated under a nitrogen atmosphere to obtain seaweed biochar-derived carbon materials.

2. The method for preparing seaweed biochar-derived carbon materials according to claim 1, characterized in that: The brown algae raw material is kelp or Sargassum fusiforme; The brown algae raw material was washed four times with deionized water, dried at 65°C, pulverized, and passed through a 100-mesh sieve to obtain the seaweed powder.

3. The method for preparing seaweed biochar-derived carbon materials according to claim 1, characterized in that: In S1, the mass ratio of the seaweed powder to water is 1:10; After the seaweed powder and water reactant is added to the sealed reactor, its liquid volume is 60% of the effective volume of the sealed reactor. Before the hydrothermal liquefaction reaction, nitrogen gas is introduced into the sealed reactor for 10 minutes, and the stirring speed during the hydrothermal liquefaction reaction is 400 r / min.

4. The method for preparing seaweed biochar-derived carbon materials according to claim 1, characterized in that: In S2, the volume ratio of the liquid product to ethyl acetate is 1:2 for each extraction, and the extraction is performed a total of 3 times. The organic phases obtained from each extraction were combined and ethyl acetate was removed under reduced pressure to obtain the oil phase product. The aqueous phases obtained from each extraction are combined, and the residual organic phase is removed to obtain the aqueous product.

5. The method for preparing seaweed biochar-derived carbon materials according to claim 1, characterized in that: In S3, the pH of the aqueous product is adjusted using hydrochloric acid with a concentration of 1 mol / L; The pH-adjusted aqueous phase solution was allowed to stand at 35°C for 60 minutes.

6. The method for preparing seaweed biochar-derived carbon materials according to claim 1, characterized in that: In S4, the ratio of sodium-based bentonite to aqueous treatment solution is 1g:20mL; After adding the sodium-based bentonite to the aqueous treatment solution, the mixture was stirred at 45°C for 8 hours, and the pH of the system was maintained at 4.0 by adding hydrochloric acid. After stirring, the mixture was allowed to stand at 40°C for 24 hours, and the solid obtained from the solid-liquid separation was washed three times with deionized water at pH 4.

0.

7. The method for preparing seaweed biochar-derived carbon materials according to claim 6, characterized in that: In S4, the solid-liquid separation is performed by centrifugation at a speed of 5000 r / min for a time of 10 min.

8. The method for preparing seaweed biochar-derived carbon materials according to claim 1, characterized in that: In S5, the mass ratio of the oil phase product to ethanol is 1:4; The oil phase diluent was added over a period of 45 minutes, and the stirring speed during the addition process was 500 r / min. After the addition was completed, stirring was continued at 60°C for 60 min, and ethanol was removed under reduced pressure at 60°C to obtain the oil-phase supported composite precursor.

9. The method for preparing seaweed biochar-derived carbon materials according to claim 1, characterized in that: In S6, the flow rate of nitrogen gas is 150 mL / min; The temperature is increased to the heat treatment temperature at a heating rate of 3℃ / min; After the heat preservation is completed, the material is cooled to below 80°C in a nitrogen atmosphere, then taken out, ground, and passed through a 100-mesh sieve to obtain the seaweed biochar-derived carbon material.